2011
DOI: 10.1603/en10200
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Egg Physiologies in Two Closely Related Grasshopper Species:Taeniopoda equesversus Romalea microptera (Orthoptera: Romaleidae)

Abstract: We compared egg survivorship and egg development time at different soil moistures for two closely related grasshopper species from divergent habitats: marsh-inhabiting Romalea microptera (Beauvois) versus desert-inhabiting Taeniopoda eques (Burmeister). These two species can interbreed and produce viable offspring. In nature, both species have a similar 8–9 mo subterranean egg stage, but their soil environments differ dramatically in water content. We predicted that the eggs of the two species would exhibit di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 70 publications
(96 reference statements)
0
6
0
Order By: Relevance
“…Egg cups were sealed with a tight-fitting lid and stored on open shelves in the laboratory at 26 ± 1.5 o C; we periodically opened and added small amounts of tap water to the cups to maintain the sand at approximately 7% moisture level. In the laboratory, pods begin to hatch 4.5 to 6.5 months after laying, and individual pods may continue hatching for 1 to 3 weeks (Stauffer et al 2011). Individual eggs can be as deep as 9 cm under the ground, and this depth causes some vermiform (fresh-hatched) nymphs to die before reaching the surface.…”
Section: Methodsmentioning
confidence: 99%
“…Egg cups were sealed with a tight-fitting lid and stored on open shelves in the laboratory at 26 ± 1.5 o C; we periodically opened and added small amounts of tap water to the cups to maintain the sand at approximately 7% moisture level. In the laboratory, pods begin to hatch 4.5 to 6.5 months after laying, and individual pods may continue hatching for 1 to 3 weeks (Stauffer et al 2011). Individual eggs can be as deep as 9 cm under the ground, and this depth causes some vermiform (fresh-hatched) nymphs to die before reaching the surface.…”
Section: Methodsmentioning
confidence: 99%
“…The response of the egg hatching rate to soil moisture clearly differed from that of egg hatching time and egg water content in the three grasshopper species. The distinct responses of grasshopper eggs reflect species-specific ecological traits associated with their phenology and habitat use (Stauffer et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, a two-stage temperature regime was not used and the development stage of the eggs at inundation was not reported. Most strikingly, Stauffer et al ( 2011 ) reported that 64% of eggs of the grasshopper, Romalea microptera , survived 90 days of submersion in sand at a relatively high 24–28°C. However, this species has a very different life history compared with C. terminifera (e.g., longer development times, larger size) and inhabits salt marsh that is subject to seasonal flooding for extended periods that would be exceedingly rare in C. terminifera oviposition habitat.…”
Section: Discussionmentioning
confidence: 99%